Pemasaran Pariwisata Kota Bogor Melalui Media Promosi Website - Asep Candra Hidayat (Majalah Ilmiah Bijak, 2017)
To succeed pwiriwisata in the city of Bogor, the local government of Bogor City Government is currently intensively doing promotional activities, including through the Web Site. To see the extent of the success of promotional efforts through the Website, then conducted a study on the people of Bogor City to assess their perceptions.The approach used in this research is quantitative approach, that is by using calculation with Likert scale. The population includes tourists and potential tourists who have / ever, and will visit the city of Bogor, both in the city of Bogor and outside the city of Bogor. The number of population can not be predicted with certainty. Sampling technique in this research is using accidental sampling method, with the number of samples taken as many as 33 people according to the number of people who successfully met and willing to fill out the questionnaire when done research. Data Collection Technique done in 2 way that is through questioner and documentation. Data Analysis Technique uses the average value formulaThe results showed that the marketing of Bogor City tourism through the Web Site is very good, it can be seen from the average score of service quality of 3.87 are included in either category. Nevertheless, there are still some assessment components that need to be improved: "Post-Visit Trip Interaction" and "Full Tour Information"